Variedades Riemannianas compactas e homogêneas com curvatura estritamente positiva - Estela Garcia Organista (2018)
In this work we present some properties of compact homogeneous Riemannian manifolds. The results presented and developed here were extracted mostly from the paper of Nolan R. Wallach, Compact homogeneous Riemannian manifolds with stric- tly positive curvature. Annals of Mathematics, Vol. 96, pp.277-295, 1972. Throughout the study is used several tools of the theory of Riemannian manifolds, Lie algebras and Lie groups. The objective of this work is to present the classification of compact homogeneous Riemannian manifolds of even dimension that admit strictly positive curvature